The effects of ten weeks block and reverse periodization training on swimming performance and body composition of moderately trained female swimmers - Arroyo-Toledo, J. J.; Clemente, V. J.; González-Ravé, J. M. (Journal of Swimming Research, 2013)
The aim of the present study was to analyze the change in competitive times of a 100m (t100c) front crawl swim performance and body composition values, after 10 weeks of assessing twenty moderately trained female swimmers,divided into two groups of training - Block periodization (BP) and reverse periodization (RP). The two groups performed identically in terms of group began theirtraining program performing aerobic trainingfrom weeks 1 to 4 and changed training to high-intensive interval training inweeks 5 to 8. The RP group began theirprogram of high-intensive interval trainingfrom weeks 1 to 4 and changedtoaerobic trainingfrom weeks 5 to 8. Both groups completed identical programs of training reduction (Taper) during weeks 9 and 10. Evaluations were made beforethe beginning of the program (T1), at the 4th week after the beginning of the swimming training (T2), at the 8th week (T3), and at the10th week (T4). Results how RP decreases significantly (p<0.05) in t100c, after 10 weeks of training, and BP decreases significantly (p<0.05) in terms of body composition values. Accordingly, it is concluded that RP indicates successresults in competition performance, and BP is a preferred option to improve body composition values in moderately trained female swimmers.